2007
DOI: 10.1111/j.1365-2567.2007.02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β2‐microglobulin‐free, disulphide‐linked HLA‐G5 homodimers in human placental villous cytotrophoblast cells

Abstract: Summary Human leucocyte antigen‐G (HLA‐G) is a natural immunosuppressant produced in human placentas that binds differently to the inhibitory leucocyte immunoglobulin‐like receptors LILRB1 (ILT2) and LILRB2 (ILT4) according to its biochemical structure. To predict the binding functions of the HLA‐G5 soluble isoform synthesized in placental villous cytotrophoblast (vCTB) cells, we investigated structural features of this protein. Biochemical and immunological studies showed that vCTB cell HLA‐G5 heavy (H)‐chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 40 publications
1
84
0
Order By: Relevance
“…Notably, none of the available studies of sHLA-G has reported what fraction of the recombinant sHLA-G produced in bacteria or of the naturally occurring sHLA-G reportedly found in fetal placenta and maternal serum is monomer or dimer. Previously full-length recombinant HLA-G (G1) produced in bacteria has been shown to form the dimer (13) as has sHLA-G (G5) reported to be produced by villous trophoblast (41).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, none of the available studies of sHLA-G has reported what fraction of the recombinant sHLA-G produced in bacteria or of the naturally occurring sHLA-G reportedly found in fetal placenta and maternal serum is monomer or dimer. Previously full-length recombinant HLA-G (G1) produced in bacteria has been shown to form the dimer (13) as has sHLA-G (G5) reported to be produced by villous trophoblast (41).…”
Section: Discussionmentioning
confidence: 99%
“…Both isoforms are present at the placental interface on trophoblasts except for HLA-G7, and the HLA-G1 and HLA-G5 are the most frequently observed. HLA-G was described as a key physiological mediator of maternal-fetal tolerance (38)(39)(40)(41). HLA-G inhibits multiple immune cell functions, including cytolytic functions of uterine and peripheral blood NK cells, Ag-specific cytolytic functions of cytotoxic T lymphocytes, allo-responsiveness of CD4 influence induction of DC tolerance (44).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G5 is able to bind b 2 -microglobulin and form dimers (16). Soluble HLA-G5, designated in this study as HLA-G5, has been reported by several groups to be produced by extravillous and villous trophoblast (15,(17)(18)(19)(20). One major HLA-G receptor described to date is ILT2, also designed leukocyte Ig-like receptor (LILR)B1 or CD85j.…”
mentioning
confidence: 99%